Characterization of canine mastocytoma cell response to cryoablation - Kimberly L Santucci; Kristi K Snyder; Robert G Van Buskirk; John G Baust; John M Baust (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
Introduction: Mastocytoma Tumors (MCT) represent 16%-21% of all skin cancers in dogs, making it the most common form of cutaneous cancer. Solitary MCT are typically treated with wide surgical excision margins. While effective, MCT excision can cause the release of a large amount of histamine and other cytokines resulting in complications such as systemic shock or anaphylaxis. Treatments such as chemotherapy and radiotherapy have been considered to achieve complete remission. Cryoablation also represents a potential treatment option for MCT. While studies have shown cryoablation to be beneficial for the treatment of numerous cancers in animals and humans, few studies have described the use of cryoablation to treat MCT's. The limited use of cryoablation is due to a number of factors including a lack of basic information pertaining to dosing (minimal lethal temperature) necessary to destroy MCT cancer. As such, in this study we conducted a series of in vitro studies using the C2 cell line and a pilot ex vivo fine needle aspirate tissue sample in an effort to detail the effects of freezing of canine MCT.  Methods: Samples were exposed to temperatures ranging from -5°C to -25°C, modeling the periphery of a cryogenic lesion for 3, 5 and 10minutes, and various markers of viability and modes of cell death were assessed daily over a 3 days recovery period. Additionally, investigation of the involvement of apoptosis in MCT cell death flowing freezing was conducted via immunoblotting and caspase inhibition studies.  Results: Viability studies revealed the -25°C isotherm as the critical minimal lethal temperature to achieve complete MCT cell death regardless of hold time. As the hold time at temperatures of -15°C and -20°C increased from 3 to 10minutes the level of cell death was also found to increase. Fluorescence microscopy, caspase inhibition and protein analysis revealed necrosis to be the primary mode of cell death following freezing. These studies, however, also revealed a significant level of apoptotic cell death post-freeze. Molecular analysis suggested that freezing to -15°C to -20°C resulted in the activation of mitochondrial mediated apoptosis 4 to 8 hours post freeze.  Conclusions: In summary, this in vitro study was designed as a first step investigation into the sensitivity of MCT cancer to freezing. These in vitro results suggest that freezing to temperatures of ≤-20°C results in a high degree of MCT cell destruction. Further the data suggest that both apoptosis and necrosis play an important role in cell death following cryoablation. These data may have translational application to MCT treatment in vivo.